Effects of preconditioning over history effects in skeletal muscles of rat - Ertugay, Yusuf Turgay. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2010., 2010)
It has been already known that activity at high lengths, leads at least, to major decreases of active force at low lengths, whereas forces at high length are hardly changed. This impact on muscle force is named as length-history effects. And it has been experienced that such effects can be minimized by a method called preconditioning in which alternating contractions are done at high and low lengths until no further decreases of active force at low lengths are seen. However, whether preconditioning does minimize the history effects or not, has not been investigated systematically in any studies so far. One of the goals of this study is to be able to observe the effects of history effects in repeated measurements by taking control measurements. Another aim of this work is to assess the effects of preconditioning over history effects in rat muscles. In order to achieve this goal, length force graph was obtained on the extensor digitorium longus (EDL) as well as to that of its synergistic muscles i.e., TA+EHL complex. Then preconditioning was performed. After that, three more length force graphs were obtained again to quantify the changes to the forces produced by these muscles. In this study, it was found that preconditioning helps to minimize the history effects in EDL distal tendon. In contrast to EDL distal, control measurement shows that preconditioning performed by EDL lengthening distally is not a solution for force decreases in EDL proximal although after preconditioning EDL muscle seems history-free. On the basis of results obtained from TA+EHL complex, the measurements taken from neighboring muscle is reliable for analysis. As a result, it can be said that any studies involving control measurement should perform preconditioning to minimize history effects. Our results therefore provide a better way to minimize the history effects for the scientists designing muscular mechanics experiments involving rat muscles.|Keywords: Length-history effects, Preconditioning, Extensor Digtorum Longus, Rat
Keywords: Musculoskeletal system.